Google Classroom as Educational Communication Media (Study at SMA Negeri 2 Percontohan Karang Baru) - Afriani Eka Mulyana; Ratri Candrasari (FISIP Universitas Malikussaleh, 2021)
This study aims to determine the role of Google Classroom as an alternative media in SMA Negeri 2 Percontohan Karang Baru. Google Classroom is an example of new media that is now widely used in education. This Google Classroom also has many features that make it easier for users to carry out the learning process even though it is not face-to-face. Teachers and students who use Google Classroom also find it helpful to have features that make the learning process easier at SMA Negeri 2 Percontohan. This study used a descriptive qualitative approach, with research data collected through observation, semi-structured interviews with several informants, and documentation. At SMA Negeri 2 Percontohan, teachers play an active role in the establishment f an effective communication process during the learning process. The results showed that the use of Google Classroom in SMA Negeri 2 Percontohan Karang Baru had a positive impact and was quite effective. Both teachers and students admit that it is not too difficult to use Google Classroom as beginners. Teachers and students also feel helped to do online learning with this Google Classroom. The features in Google Classroom are also easy to use. ABSTRAKPenelitian ini bertujuan menggambarkan peran Google Classroom sebagai media alternatif pada SMA Negeri 2 Percontohan Karang Baru. Google Classroom merupakan salah satu contoh new media yang sekarang banyak dipergunakan dalam pendidikan. Google Classroom memiliki banyak fitur yang memudahkan pengguna dalam melakukan proses pembelajaran walaupun tidak melalui tatap muka secara langsung. Guru dan murid yang menggunakan Google Classroom juga merasa terbantu dengan adanya fitur yang memudahkan proses pembelajaran di SMA Negeri 2 Percontohan. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dimana data dikumpulkan melalui observasi, wawancara semi terstruktur, dan dokumentasi. Temuan lapangan yaitu para guru di SMA Negeri 2 Percontohan berperan aktif dalam terjalinnya proses komunikasi yang efektif selama proses pembelajaran. Penggunaan Google Classroom di SMA negeri 2 Percontohan Karang Baru memiliki dampak positif dan cukup efektif. Selama proses pembelajaran guru dan siswa sama-sama mengaku bahwa tidak terlalu sulit dalam menggunakan Google Classroom ini sebagai pemula. Guru dan siswa juga merasa terbantu melakukan pembelajaran secara daring dengan adanya Google Classroom. Fitur-fitur yang ada pada Google Classroom juga mudah digunakan.